2017
DOI: 10.1523/jneurosci.1825-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional NMDA Receptor Signaling

Abstract: In the classical view, NMDA receptors (NMDARs) are stably expressed at the postsynaptic membrane, where they act via Ca to signal coincidence detection in Hebbian plasticity. More recently, it has been established that NMDAR-mediated transmission can be dynamically regulated by neural activity. In addition, NMDARs have been found presynaptically, where they cannot act as conventional coincidence detectors. Unexpectedly, NMDARs have also been shown to signal metabotropically, without the need for Ca This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 116 publications
(95 reference statements)
2
102
0
Order By: Relevance
“…The induction of LTP and LTD involves activation of NMDA receptors, Ca 2+ entry, and differential activation of kinases/phosphatases [18]. Interestingly, recent work indicates that amyloid beta could act on GluN2B subunits, through metabotropic mechanisms, to influence phosphatase/kinase activity, influencing synaptic function and spine loss [48,49]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of LTP and LTD involves activation of NMDA receptors, Ca 2+ entry, and differential activation of kinases/phosphatases [18]. Interestingly, recent work indicates that amyloid beta could act on GluN2B subunits, through metabotropic mechanisms, to influence phosphatase/kinase activity, influencing synaptic function and spine loss [48,49]. …”
Section: Introductionmentioning
confidence: 99%
“…In turn, a decrease in NMDA receptor function is likely to influence induction of AMPA receptor mediated synaptic plasticity [48,58] (i.e. metaplasticity [59]).…”
Section: Introductionmentioning
confidence: 99%
“…Next, we found that NYX‐2925 pretreatment enhanced activity‐dependent synaptic insertion of α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptors (AMPARs). Given the NYX‐2925 dose–response profile and increasing appreciation of non‐ionotropic modes of NMDAR signal transduction (Dore et al ), this study demonstrates that NYX‐2925 is a powerful tool to probe both canonical and novel modes of NMDAR signaling.…”
mentioning
confidence: 77%
“…Together with this literature, our findings support the conclusion that NYX‐2925 may modulate synaptic NMDAR levels via metabotropic‐like signaling of the NMDAR. As reviewed by Dore and colleagues (Dore et al ), the existence and biological relevance of metabotropic NMDAR signaling is an active area of research with several investigators finding both supportive (Yang et al ; Kessels et al ; Nabavi et al ; Tamburri et al ; Dore et al ; Kim et al ; Stein et al ) and contradictory (Babiec et al ; Volianskis et al ; Sanderson et al ) evidence. Among the former, several studies have revealed ion flux‐independent trafficking of GluN2‐containing NMDARs both by NMDAR agonists (Vissel et al ; Barria and Malinow ) and by co‐agonists (Nong et al ; Ferreira et al ).…”
Section: Discussionmentioning
confidence: 99%
“…3,10 Unlike other ionotropic glutamate receptors found in the brain, such as α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid or kainic acid receptors, the NMDARs are unique in that they have distinct binding sites for both glutamate and glycine, and binding of both ligands is required for receptor activation. 6 In addition to their pivotal role in physiological CNS-related processes, NMDARs seem to be crucially involved in numerous CNS disorders, including anxiety, 11,12 schizophrenia, 6,[13][14][15] ischemic stroke, 6,13,16 Parkinson disease, 6,12 and chronic pain conditions, such as neuropathic pain 4,10,16 and fibromyalgia. 17,18 The potency (half-maximal effective concentration) of NYX-2925 was 0.028-55 pM when measured against NMDAR subtypes, NR2A-D, in human embryonic kidney cells expressing human recombinant NMDA receptors.…”
Section: Study Highlightsmentioning
confidence: 99%